Clinical and Prognostic Value of Immunogenetic Characteristics in Anti-LGI1 Encephalitis. Issue 3 (May 2021) - Muñiz-Castrillo, Sergio; Haesebaert, Julie; Thomas, Laure; Vogrig, Alberto; Pinto, Anne-Laurie; Picard, Géraldine; Blanc, Charlotte; Do, Le-Duy; Joubert, Bastien; Berzero, Giulia; Psimaras, Dimitri; Alentorn, Agusti; et al.
Abstract : Objective: Antibodies against leucine-rich glioma-inactivated 1 (LGI1-Abs) characterize a limbic encephalitis (LE) strongly associated with HLA-DRB1*07:01, although some patients lack LGI1-Abs in CSF or do not carry this allele. Whether they represent a different subtype of disease or have different prognoses is unclear. Methods: Retrospective analysis of clinical features, IgG isotypes, and outcome according to LGI1-Ab CSF positivity and DRB1*07:01 in a cohort of anti-LGI1 LE patients. Results: Patients with LGI1-Abs detected in both CSF and serum (105/134, 78%) were compared with those who were CSF negative (29/134, 22%). Both groups had similar clinical features and serum levels, but CSF-positive patients had shorter diagnostic delay, more frequently hyponatremia, inflammatory CSF, and abnormal MRI ( p < 0.05). Human leukocyte antigen (HLA) genotyping was performed in 72/134 (54%) patients and 63/72 (88%) carried DRB1*07:01. Noncarriers (9/72, 12%) were younger, more commonly women, and had less frequently psychiatric and frontal symptoms ( p < 0.05). No difference in IgG isotypes according to CSF positivity or HLA was found ( p > 0.05). HLA and IgG isotypes were not associated with poor outcome (mRS >2 at last follow-up) in univariate analyses; CSF positivity was only identified as a poor outcome predictor in the multivariate analysis including the complete follow-up, whereas age and female sex also remained when just the first year was considered. Conclusions: LE without CSF LGI1-Abs is clinically indistinguishable and likely reflects just a lesser LGI1-Ab production. HLA association is sex and age biased and presents clinical particularities, suggesting subtle differences in the immune response. Long-term outcome depends mostly on demographic characteristics and the intensity of the intrathecal synthesis.